Celebrating Divine Mystery : A Primer in Liturgical Theology - Vincie, Catherine, 1951- (Book collections on Project MUSE., 2009)
"In this primer, Catherine Vincie introduces readers to current liturgical theology by providing them with the foundational themes of the field. She explains that liturgy draws us into the paschal mystery of Jesus Christ, that it should create a space in which we attempt to name toward God by employing an abundance of metaphors and images, and that the sacraments are communicated and understood through the use of symbols. Vincie is grounded in the liturgical reforms of the Second Vatican Council. As such, Celebrating Divine Mystery seeks to draw readers into "full, conscious, and active participation" in the liturgy by informing them about recent scholarship and challenging them to enter the divine mystery as informed and engaged participants."--BOOK JACKET.